Enhancement in Ti–6Al–4V sintering via nanostructured powder and spark plasma sintering. (April 2014) - Crosby, K.; Shaw, L. L.; Estournes, C.; Chevallier, G.; Fliflet, A. W.; Imam, M. A.
Abstract : Studies are performed to enhance low temperature sintering of Ti–6Al–4V. High energy ball milling is found to be effective in lowering the sintering temperature through the mechanisms of particle size reduction and nanograin formation. The former reduces the diffusion distance for densification, whereas the latter introduces an additional densification mechanism allowing mass transport from the interior of the particle to the neck zone. Together, these two effects can reduce the onset temperature for densification by about 300°C. Spark plasma sintering can further improve low temperature sintering when compared with radiant heat sintering and microwave sintering. The enhanced densification is discussed on the basis of the applied pressure (50 MPa) and the intrinsic joule effect that leads to increase in the local temperature at the contact point between particles.